Karl Fischer Titration as An Alternative Method for Determing The Water Content of Indonesian Spices - Wahyu Supartono (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1999)
Karl Fischer Titration (KFT) is a well established and effective direct primary method to determine water content in various materials. It is based on a specific chemical reaction and it differs principally from the drying and distillation methods. The KFT was introduced as an alternative method to determine the water content in some Indonesian spices (clove, coriander, ginger and white pepper), which generally contain appreciable amount of volatile compounds to distract accurate moisture. The samples used were prepared by cutting and grinding with a morser. The KFT system used was one-component reagent with methanol as working medium. The samples were introduced into a KFT titration cell and titrated directly with the KFT reagent. The extraction time of determination was 60 seconds. The determination of the water content took approximately 10-20 minutes. The distillation and drying method served as control or reference method. The distillation methods which used was a mixture of toluene and xylene 95:5 (vlv) took 2 hours. The drying method was conducted at temperature of 105°C for 3-4 hours.